2018
DOI: 10.1002/zaac.201800354
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Kinetic Stabilization of a Ce4+‐based MOF by in‐situ Powder X‐ray Diffraction

Abstract: We herein investigated the synthesis of the Ce4+‐based metal‐organic framework [Ce6(μ3‐O)4(μ3‐OH)4(PZDC)4(OH)4(H2O)4] denoted as Ce‐DUT‐67‐PZDC (where DUT stands for Dresden University of Technology and PZDC2– stands for 3,5‐pyrazoledicarboxylate) by in‐situ powder X‐ray diffraction methods under solvothermal conditions using synchrotron radiation. It was observed that the obtained MOF is rapidly formed between 120 and 140 °C, but only as an intermediate product in this preparative system. After prolonged reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…Besides structural defects, it is also likely that small amounts of reduced Ce 3+ ions are present in the materials. It has been reported that the synthesis solvent can reduce Ce 4+ of the cluster, ultimately leading to Ce 3+ containing MOFs or side products . XANES analysis of a Ce 6 ‐MOF has shown that up to 1 Ce 3+ ion per cluster can be present without any loss of structural integrity .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides structural defects, it is also likely that small amounts of reduced Ce 3+ ions are present in the materials. It has been reported that the synthesis solvent can reduce Ce 4+ of the cluster, ultimately leading to Ce 3+ containing MOFs or side products . XANES analysis of a Ce 6 ‐MOF has shown that up to 1 Ce 3+ ion per cluster can be present without any loss of structural integrity .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the synthesis solvent can reduce Ce 4+ of the cluster, ultimately leading to Ce 3+ containing MOFs or side products. [41,42] XANES analysis of a Ce 6 -MOF has shown that up to 1 Ce 3+ ion per cluster can be present without any loss of structural integrity. [43] The following time-resolved single crystal fluorescence microscopy experiments will provide insights on their presence and impact.…”
Section: Ce-cau-24-tbapy Mofmentioning
confidence: 99%
“…. 31 Therefore, future efforts will be aimed at upscaling the synthetic protocol using CAN and HNO3. The fact that the reaction temperature (60 °C) is well below the normal boiling point of water is a great advantage for upscaling, because there is no need for sophisticated, pressure resistant vessels.…”
Section: Ex Situ Optimisation Of F4_mil-140a(ce) Synthesismentioning
confidence: 99%
“…30 The synthesis of these MOFs is typically carried out in N,N-dimethylformamide (DMF)/water mixtures as a reaction medium and in situ XRD studies have been key in revealing how the desired product is completely crystallised within a few minutes. 31 However, this phase is metastable and, if left in the reaction environment, undergoes dissolution to form Ce(III)-formate, having formula Ce(O2CH)3. Formation of Ce(III)-formate was attributed to the reaction between Ce(III), derived from reduction of Ce(IV) in solution, and formate generated by hydrolysis of DMF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation